Civil society, environmental litigation, and Confucian energy justice: A case study of an environmental NGO in China. (November 2022) - Wang, Xinxin; Lo, Kevin
Abstract: This study analyzes the role of civil society in China's clean energy transition from the perspective of Confucianism, an influential political-ethical doctrine with over 2000 years of history. An environmental non-governmental organization (ENGO), Friends of Nature (FON), was taken as a case study. FON is a pioneering ENGO in China and has become an influential actor in low-carbon energy transition in the country, primarily through its environmental litigation on energy projects. We argue that FON's legal actions, which focus on the climate and sustainability aspect of energy, are embedded in a Confucian understanding of justice, that is, justice as the pursuit of collective interest rather than the fair treatment of individuals; justice as nature-humanity harmony and the conservation of natural resources for future generation; and justice as an important manifestation of Confucian self-cultivation and a political obligation. This study contributes to the broader energy justice literature by proposing an understanding that goes beyond its Western origin.